Midkine Deteriorates Cardiac Remodeling via Epidermal Growth Factor Receptor Signaling in Chronic Kidney Disease. Issue 5 (May 2016) - Honda, Yuki; Shishido, Tetsuro; Takahashi, Tetsuya; Watanabe, Tetsu; Netsu, Shunsuke; Kinoshita, Daisuke; Narumi, Taro; Kadowaki, Shinpei; Nishiyama, Satoshi; Takahashi, Hiroki; Arimoto, Takanori; Miyamoto, Takuya; et al.
Abstract : In chronic kidney disease, activation of the epidermal growth factor receptor (EGFR) leads to cardiac hypertrophy, which affects morbidity and mortality. In patients with renal insufficiency and heart failure, the expression of midkine, a heparin-binding growth factor, is increased. Therefore, we investigated the association between midkine and EGFR in the induction of cardiac hypertrophy and dysfunction in chronic kidney disease. We performed subtotal nephrectomies in midkine-knockout mice and wild-type mice. We found that subtotal nephrectomy-induced cardiac hypertrophy and phosphorylation of extracellular signal–regulated kinase 1/2 and AKT were attenuated in midkine-knockout mice compared with wild-type mice. An antiphosphotyrosine receptor antibody array was used to demonstrate that EGFR phosphorylation in the heart was also lower in midkine-knockout mice than in wild-type mice. Midkine induced EGFR, extracellular signal–regulated kinase 1/2, and AKT phosphorylation and led to hypertrophy in neonatal rat cardiomyocytes. Pretreatment with EGFR inhibitors or EGFR silencing suppressed midkine-stimulated phosphorylation of extracellular signal–regulated kinase 1/2 and AKT, induction of fetal cardiac gene expression, and hypertrophy in cardiomyocytes. To confirm the association between midkine and EGFR in vivo, mice subjected to subtotal nephrectomy were treated with the EGFR inhibitor gefitinib. Gefitinib treatment attenuated subtotal nephrectomy-induced cardiac hypertrophy. These results indicate that midkine might be a key mediator of cardiorenal interactions through EGFR activation, which plays a crucial role in cardiac hypertrophy in chronic kidney disease. Abstract : Supplemental Digital Content is available in the text.